2020
DOI: 10.2147/ott.s266344
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reactive Oxygen Species Modulator 1 is Associated with Poor Survival in Patients with Non-Small Cell Lung Cancer After Stereotactic Fractionated Radiosurgery: A Retrospective Pilot Study</p>

Abstract: Purpose: It has been reported that the overexpression of reactive oxygen species modulator 1 (Romo1) is significantly associated with poor survival outcomes in patients with lung cancer who received surgical resection, conventional fractionated radiotherapy, and chemotherapy. In this study, we investigated whether Romo1 expression is associated with survival outcomes in patients with early-stage lung cancer who were treated with radiosurgery. Methods: Romo1 protein expression was evaluated and scored in the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“… 19 , 20 According to recent studies, Romo1 was associated with early recurrence or metastasis of lung cancer treated with radiotherapy. 21 , 22 These results consistently support that Romo1 can be a promising predictive and prognostic biomarker in various treatment settings for malignancies. However, the clinical implications of serum Romo1 in patients with cancer are still unclear.…”
Section: Introductionsupporting
confidence: 63%
“… 19 , 20 According to recent studies, Romo1 was associated with early recurrence or metastasis of lung cancer treated with radiotherapy. 21 , 22 These results consistently support that Romo1 can be a promising predictive and prognostic biomarker in various treatment settings for malignancies. However, the clinical implications of serum Romo1 in patients with cancer are still unclear.…”
Section: Introductionsupporting
confidence: 63%
“…The detailed methods of initial diagnosis and pretreatment evaluation have been described in our previous studies. 17 , 18 Briefly, pretreatment evaluation consisted of complete history and physical examination, basic laboratory studies, pulmonary function test, electrocardiogram, transthoracic echocardiogram, chest radiography, chest computed tomography (CT) scan, brain magnetic resonance imaging, bone scan, and positron emission tomography (PET). The HbA1c levels of all patients were checked 1 week before the start of radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Table 6 summarizes these previous studies and the present data, evaluating the clinical implications of Romo1 in lung cancer patients. Different studies have demonstrated different cutoffs from each other; however, the low H score cutoffs in two studies (11,30) can be attributed to the early stage population enrolled in those studies. The present data suggest that Romo1 levels seem to be abundant in advanced disease.…”
Section: Discussionmentioning
confidence: 93%
“…Romo1 is a major regulator of intracellular ROS production, and Romo1-induced ROS are indispensable for the proliferation of normal and cancer cells ( 6 , 7 ). Studies have consistently demonstrated the potential value of Romo1 as a novel biomarker for various lung cancer treatment ( 11 , 12 , 29 , 30 ). Table 6 summarizes these previous studies and the present data, evaluating the clinical implications of Romo1 in lung cancer patients.…”
Section: Discussionmentioning
confidence: 98%